2009
DOI: 10.1002/bmc.1203
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fenofibric acid in human plasma by ultra performance liquid chromatography–electrospray ionization mass spectrometry: application to a bioequivalence study

Abstract: A rapid, specific and sensitive ultra-performance liquid chromatography tandem mass spectrometry method was developed for the determination of fenofibric acid in human plasma. The method involves simple, one-step liquid-liquid extraction procedure coupled with an Acquity UPLC(TM) BEH C(18) column (50 x 2.1 mm, i.d., 1.7 microm) with isocratic elution at a flow-rate of 0.2 mL/min and mefenamic acid was used as the internal standard. The Quattro Premier XE mass spectrometry was operated under the multiple reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
0
18
1
Order By: Relevance
“…The favorable pharmacokinetic properties of fenofibrate as well as its known safety and tolerability (3,28) suggest that it might have future clinical application. Its use may be restricted to combination with other established drugs such as artemisinin derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…The favorable pharmacokinetic properties of fenofibrate as well as its known safety and tolerability (3,28) suggest that it might have future clinical application. Its use may be restricted to combination with other established drugs such as artemisinin derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] A more recent study showed that the utilization of HPLC with tandem MS for the quantitation of fenofibric acid in plasma improved the LOQ, being 0.16 nmol/mL of plasma. 19) However, to our knowledge, the LOQ for fibric acids in liver samples have not been reported. Low LOQ in liver samples is important when Fibric acid (0.5, 2.5 or 20 nmol) was added to liver homogenates (10 mg of liver).…”
Section: Methods Validationmentioning
confidence: 84%
“…The high sensitivity to quantitate fibric acids without interference from liver components enable this method to be successfully applied to quantitate fibric acids in very small portions of the liver of rats treated with fibrates. A recently reported method, which employs HPLC with tandem MS detection, 19) seems to be more sensitive than our proposed method, but the method requires a tandem MS detector. The high sensitivity and simplicity of the presently described method to determine fibric acids should accelerate quantitative studies on the mechanisms underlying the bioactive action of fibric acids in tissues.…”
Section: Application Of the Methods To Actual Analysis Of Liver Samplesmentioning
confidence: 89%
See 1 more Smart Citation
“…Fenofibrate is official in USP (11) and BP (12) but different methods have been cited in the literature for determination of fenofibrate involving HPLC-UV (13,14) and HPLC-MS (15), voltammetry (16) and differential pulse polarographic techniques (17). A stability indicating UPLC method for simultaneous determination of atorvastatin, fenofibrate and their impurities in tablets was developed and validated (14).…”
mentioning
confidence: 99%